2012
DOI: 10.1021/cm202125q
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Enzyme Immobilization and Stabilization within Meso-Structured Onion-Like Silica for Biodiesel Production

Abstract: Meso-structured onion-like silica (Meso-Onion-S) was synthesized and used as a host of enzyme immobilization. Meso-Onion-S has a 200–300 nm sized primary meso-structured onion building unit, and each onion unit has highly curved mesopores of 10 nm diameter in a multishell structure. Nanoscale enzyme reactors (NERs) in Meso-Onion-S were prepared via a two-step process of enzyme adsorption and subsequent enzyme cross-linking, which effectively prevents the leaching of cross-linked enzyme aggregates from highly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 38 publications
1
41
1
Order By: Relevance
“…1), and this result was in accordance with the previous reports89. The TEM image showed that the DPMS had clear multishell structures with mesopore size of about 13 nm between the layers (Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…1), and this result was in accordance with the previous reports89. The TEM image showed that the DPMS had clear multishell structures with mesopore size of about 13 nm between the layers (Fig.…”
Section: Resultssupporting
confidence: 92%
“…These advantages of mesoporous silica supports enable the improvement of activity and stability of enzymes. Recently, a novel meso-structured onion-like silica (Meso-Onion-S), which had highly curved mesopores and highly ordered onion-like multilayer, was synthesized and used as a host for the immobilization of enzyme, and the stability of the enzyme was effectively improved89. However, there are only two reports regarding the study of Meso-Onion-S, and therefore further studies for the immobilization of enzyme in this novel porous material are indeed required.…”
mentioning
confidence: 99%
“…Immobilized lipase in NERs represented more stability during 40 days but free cells showed a rapid inactivation. Specific activity of immobilized lipase was higher than free cells (Jun et al 2012).…”
Section: Biodiesel Productionmentioning
confidence: 77%
“…c o m / l o c a t e / f u e l application of homogeneous catalysts (NaOH, KOH) had been restricted by several serious challenges including environmental pollution and separating difficulty [8]. During the past several decades, heterogeneous catalysts, which were consisted of solid acids and solid bases, such as metal oxides, composite metal oxides, zeolites, hydrotalcites, anion exchange resins and lipase immobilized on various supports [9][10][11][12][13][14], were considered as promising catalysts in transesterification reactions. In a word, both solid acids and solid bases were reported to be used for the transesterification [15,16].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%